Peran Citra Merek Dalam Memediasi Pengaruh Kualitas Produk Terhadap Niat Beli Ulang Pada E-Commerce Sayurbox di Kota Denpasar - Kevin Bryan Anantha; Ni Ketut Seminari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to investigate the role of brand image in mediating the relationship between product quality and consumer purchase intention in Sayurbox e-commerce. Data was collected through a survey from Sayurbox consumers in Denpasar, Bali. The analysis results indicate that product quality has a significant positive influence on repeat purchase intention. Additionally, product quality also has a positive effect on brand image. These findings suggest that products with good quality tend to form a positive brand image. Furthermore, brand image also has a positive impact on repeat purchase intention. This study provides a better understanding of the factors influencing consumer purchase intention in Sayurbox e-commerce and offers insights to enhance the shopping experience for consumers on the platform.